TEKNIK MODELING DALAM BIMBINGAN KELOMPOK UNTUK PERENCANAAN KARIER SISWA SMA - Nanin Rahmatyana; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
Career planning in high school is a student activity that leads to career decisions in the future, this decision is very influential on the choices that will be taken on the future of students. for that the existence of the school becomes a forum in helping students with career planning to be chosen. Behavior that arises from the problem of career planning is because there are still students who have an indication of the inability to plan a career for the future, so that the information created can be useful material for educators, especially BK teachers if they encounter problems regarding student career planning. For this reason, this literature study uses modeling techniques in group guidance to help with student career planning. The purpose of this research is to be able to help students find interest in their career choices presented in groups and find models that can be used as figures to plan their careers. The method used is a literature review which collects information from previous findings and research. The results of this study can be a reference in providing group guidance modeling techniques to help with student career planning and can provide good services and can also help students in planning careers for their future. Keywords: Modeling Techniques, Group Guidance, Career Planning